2015
DOI: 10.1080/00981389.2015.1046574
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Recovery in Mental Health: Perspectives From a Muslim Culture

Abstract: This article describes the outcomes of research into how individuals with mental health problems at the National Centre of Mental Health in Jordan perceived the causes of their mental health problems, the coping strategies they employed, how they sought help, and how they experienced what is termed the process of recovery. Semi-structured interviews were conducted with 10 male and 10 female patients diagnosed with a range of mental health problems. The research suggests that each person perceived recovery uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Many participants viewed their spirituality as a journey involving phases of confusion and doubts, insights and opportunities for transformation (Mental Health Foundation, 2002). A final sub-theme Destiny v. autonomy concerned the level of choice and control people conceptualised themselves as having in relation to their religious or spiritual belief systems (Smith and Suto, 2012; Yang et al ., 2012; Eltaiba and Harries, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many participants viewed their spirituality as a journey involving phases of confusion and doubts, insights and opportunities for transformation (Mental Health Foundation, 2002). A final sub-theme Destiny v. autonomy concerned the level of choice and control people conceptualised themselves as having in relation to their religious or spiritual belief systems (Smith and Suto, 2012; Yang et al ., 2012; Eltaiba and Harries, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of Spiritual practices helped participants to cope with their mental health problems with prayer having particular significance (Al-Solaim and Loewenthal, 2011; Eltaiba and Harries, 2015). People's Spiritual relationship , whether with God, a spiritual figure or a higher spiritual power was often significant for participants, being described as central to their faith or the most important relationship of their lives with crucial importance for coping during times of illness (Lilja, et al ., 2016; Hanevik et al ., 2017; Oxhandler et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Results of different studies also show that there is a significant relationship between spiritual understanding and mental health. [16,25,26] Researches on "the effects of spirituality on health" have shown that spirituality is associated with lower amount of diseases and greater longevity. [27,28] When faced with an injury, people who have spiritual orientations respond better to treatments and better cope with injuries and defects.…”
Section: Discussionmentioning
confidence: 99%
“…22 Notably, each pillar is strongly connected to prayer and devotion, a source of strength important to recovery from illness. 23 Maintaining personal cleanliness and a clean space to pray in health care settings in the midst of illness are particular challenges. This is an important concern for Muslim patients with advanced illness who spend a good deal of time in hospitals, clinics, and other health care environments.…”
Section: Prayermentioning
confidence: 99%